Pulmonary arterial pressure at rest and during exercise in chronic mountain sickness: a meta-analysis. Issue 6 (27th June 2019) - Soria, Rodrigo; Egger, Matthias; Scherrer, Urs; Bender, Nicole; Rimoldi, Stefano F.
Up to 10% of the more than 140 million high-altitude dwellers worldwide suffer from chronic mountain sickness (CMS). Patients suffering from this debilitating problem often display increased pulmonary arterial pressure (PAP), which may contribute to exercise intolerance and right heart failure. However, there is little information on the usual PAP in these patients. We systematically reviewed and meta-analysed all data published in English or Spanish until June 2018 on echocardiographic estimations of PAP at rest and during mild exercise in CMS patients. Nine studies comprising 287 participants fulfilled the inclusion criteria. At rest, the point estimate from meta-analysis of the mean systolic PAP was 27.9 mmHg (95% CI 26.3–29.6 mmHg). These values are 11% (+2.7 mmHg) higher than those previously meta-analysed in apparently healthy high-altitude dwellers. During mild exercise (50 W) the difference in mean systolic PAP between patients and high-altitude dwellers was markedly more accentuated (48.3 versus 36.3 mmHg) than at rest. These findings indicate that in patients with CMS PAP is moderately increased at rest, but markedly increased during mild exercise, which will be common with activities of daily living. This meta-analysis shows that in high-altitude dwellers suffering from chronic mountain sickness, pulmonary hypertension, while rare at rest, is frequent during daily activities http://ow.ly/Mw8730oiZ4z